Energy absorption capability of aluminium tube partially wrapped with glass/epoxy subjected to quasi-static loading - Abbas, T. (Asian Research Publishing Network, 2016)
Thin-walled hybrid tubes developed by a combination of metal and composite merge the benefits of metal and composite that is a high axial load carrying capacity, stable collapse modes, which result in maximum total energy absorption (TEA), specific energy absorption (SEA), and crush force efficiency (CFE). The improvement in energy absorption competency of round aluminium tube, having applications in transportation vehicles as well as aircraft, is meted out throughout this examination. Impact properties for partially wrapped tube are not well addressed in all previous studies. In order to improve energy absorption features, partial wrapping and full wrapping of the circular aluminium tube with glass/epoxy by applying 90Â° fiber angle and 6 numbers of layers of composite is performed, using filament winding process. Moreover, impact properties of partially wrapped tube and fully wrapped tubes are determined by applying quasistatic loading. In addition to this, TEA, SEA, axial load carrying capacity (Pmax) and CFE are analyzed to achieve improvement in energy absorption capability of partially wrapped aluminium tube with glass/epoxy. The result revealed that SEA of partially wrapped aluminium tube is 49.09 and 14.84 more as compared with partially wrapped steel and fully wrapped aluminium tube respectively. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.